Impact of psoriasis in the quality of life of children, adolescents and their families: a cross-sectional study - SALMAN, ANDAÇ; YÜCELTEN, AYŞE DENİZ; PERDAHLI FİŞ, NEŞE (SOC BRASILEIRA DERMATOLOGIA, 2018)
BACKGROUND: Psoriasis is a chronic and inflammatory disease that impairs quality of life and causes psychological symptoms. Despite the high prevalence of psoriasis in pediatric patients, studies investigating the impact of psoriasis in the quality of life of children, adolescents and families are sparse. OBJECTIVE: To investigate the impact of psoriasis in the quality of life of children and adolescents with psoriasis and their families and to determine depression and anxiety levels of the patients. METHODS: A total of 58 patients with psoriasis aged 7-18 years (median age: 11) and a family member of each patient were included in the study. Children's Dermatology Life Quality Index (CDLQI), Family Dermatology Life Quality Index (FDLQI), Children's Depression Inventory (CDI) and State-Trait Anxiety Inventory for Children (STAIC) were used in the study. RESULTS: The median PASI score of the patients included in the study was 1.8. The median CDLQI and FDLQI scores in the study groups were 5 and 10, respectively. The median CDI score, STAIC-state and STAIC-trait scores of the patients were 6,28 and 325, respectively. STUDY LIMITATIONS: Lack of a control group and patient assessment of disease severity. Relatively mild disease severity of the subjects. CONCLUSIONS: Psoriasis has a negative impact in the quality of life of children, adolescents and their families, even in the presence of mild disease. Considering that impairment in quality of life may be associated with psychosocial morbidity, a combined approach with medical therapy, family counseling and quality of life assessment may be beneficial in this patient group.
Keywords: Adolescent; Child; Family; Psoriasis; Quality of life; PEDIATRIC-PATIENTS; SECONDARY IMPACT; INDEX CDLQI; DISEASE; IMPAIRMENT; DISABILITY; INVENTORY